Pregunta
upstudy study bank question image url

6. A function of the form \( p(x)=a x^{2}+q \) has two \( x \)-intercepts, one of which is Determine the other \( x \)-intercept and explain how you arrived at your answer. \( p(x)=a x^{2}+q \) \( 0=a x^{2}+q \) \( -q=a x^{\overline{2}} 9 \)

Ask by Schofield Fowler. in Canada
Feb 21,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The other x-intercept is at (–9, 0).

Solución

The function is given by p(x) = ax² + q, which is symmetric about the y-axis because it contains only an x² term (besides the constant). This means that if x = 9 is an x-intercept (so the point (9, 0) is on the graph), then the other x-intercept must be the mirror image with respect to the y-axis, namely (–9, 0). Here’s how we can verify this step by step: 1. To find the x-intercepts, we set p(x) = 0:   0 = ax² + q 2. Rearranging, we get:   ax² = –q   x² = –q/a 3. Taking the square root of both sides gives:   x = ±√(–q/a) Since we know one x-intercept is x = 9, it must be that:   √(–q/a) = 9 Thus, the two solutions for x are:   x = 9 and x = –9 Therefore, the other x-intercept is (–9, 0). This result makes sense intuitively because the graph of a quadratic function of the form ax² + q is symmetric about the y-axis, so the x-intercepts occur in oppositely signed pairs.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To find the other \( x \)-intercept of the function \( p(x) = ax^2 + q \), we start with the equation for the \( x \)-intercepts, which is \( 0 = ax^2 + q \). Rearranging gives us \( ax^2 = -q \). Since we are given that one of the \( x \)-intercepts is known (let's call it \( r_1 \)), we can substitute \( r_1 \) back into the equation to find \( q \). Thus, \( 0 = ar_1^2 + q \) implies \( q = -ar_1^2 \). Now, substituting this back into \( 0 = ax^2 + q\): \[ 0 = ax^2 - ar_1^2 \] Factoring gives us \( a(x^2 - r_1^2) = 0 \), which can be further factored as \( a(x - r_1)(x + r_1) = 0 \). Therefore, the other \( x \)-intercept is \( -r_1 \). So if you have one intercept at \( r_1 = 3 \), the other intercept would be \( -3 \). This neat symmetry in quadratic functions is a delightful feature of their parabolic nature! They always offer two \( x \)-intercepts that are equidistant from the vertex along the \( x \)-axis when the function has real roots.

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad